Cosmic entanglement sudden birth: expansion-induced entanglement in hydrogen atoms - Yusef Maleki; Alireza Maleki; M. Suhail Zubairy (Communications Physics)
Abstract Hydrogen is the most dominant atom in the universe and is considered the main component of baryonic matter. Thus far, the quantum features of the unbounded hydrogen atoms in the background of the universe and the possibility of emerging unique quantum effects, such as entanglement on the cosmological scale, have not been considered. In this work, we demonstrate that the dynamical expansion of the universe leads to the emergence of natural entanglement in the hyperfine structure of atomic hydrogen. Our findings reveal that there exists a critical age for the universe where hydrogen atoms naturally build up entanglement, resulting from the expansion of the universe. More precisely, when the universe reaches the age of about 2.5 × 1018 seconds (about 80 billion years old), the hyperfine structure entanglement in hydrogen atoms naturally takes off, demonstrating a peculiar quantum phenomenon known as entanglement sudden birth. This expansion-induced entanglement becomes maximum at about 3.6 × 1018 seconds (about 115 billion years), after the Big Bang. By analyzing the fate of seed atoms formed in the early universe, this study underscores the significance of unique quantum mechanical features, such as entanglement, on cosmological scales.